High Temperature Annealing of Twin-Roll Cast Al-Li-Based Alloy Studied by In-situ SEM and STEM - Cieslar, Miroslav; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Belejová, Sára; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Microscopy and Microanalysis)
Keywords: Instrumentation

Novel AgCa and AgCaLa alloys for Fe-based bioresorbable implants with adapted degradation - Krüger, Jan Tobias; Hoyer, Kay-Peter; Filor, Viviane; Pramanik, Sudipta; Kietzmann, Manfred; Meißner, Jessica; Schaper, Mirko (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Intermetallic Phase Growth in Al-steel Clad Strip during In-situ Heating in TEM - Křivská, Barbora; Šlapáková, Michaela; Minárik, Peter; Fekete, Klaudia; Králík, Rostislav; Stolbchenko, Mykhailo; Schaper, Mirko; Grydin, Olexandr (Microscopy and Microanalysis)
Keywords: Instrumentation

Investigating the microstructure of an additively manufactured FeCo alloy: an electron microscopy study - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering; Engineering (miscellaneous); General Materials Science; Biomedical Engineering

Strength enhancement of AlMg sheet metal parts by rapid heating and subsequent cold die stamping of severely cold-rolled blanks - Camberg, Alan Adam; Andreiev, Anatolii; Pramanik, Sudipta; Hoyer, Kay-Peter; Tröster, Thomas; Schaper, Mirko (Materials Science and Engineering: A)

Correlation between Taylor Model Prediction and Transmission Electron Microscopy-Based Microstructural Investigations of Quasi-In Situ Tensile Deformation of Additively Manufactured FeCo Alloy - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Journal of Materials Engineering and Performance)
Abstract Within this research, the multiscale microstructural evolution before and after the tensile test of a FeCo alloy is addressed. X-ray µ -computer tomography (CT), electron backscattered diffraction (EBSD), and transmission electron microscopy (TEM) are employed to determine the microstructure on different length scales. Microstructural evolution is studied by performing EBSD of the same area before and after the tensile test. As a result, $$\langle$$ ⟨ 001 $$\rangle$$ ⟩ ||TD, $$\langle$$ ⟨ 011 $$\rangle$$ ⟩ ||TD are hard orientations and $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ ||TD is soft orientations for deformation accommodation. It is not possible to predict the deformation of a single grain with the Taylor model. However, the Taylor model accurately predicts the orientation of all grains after deformation. {123} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the most active slip system, and {112} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the least active slip system. Both EBSD micrographs show grain subdivision after tensile testing. TEM images show the formation of dislocation cells. Correlative HRTEM images show unresolved lattice fringes at dislocation cell boundaries, whereas resolved lattice fringes are observed at dislocation cell interior. Since Schmid’s law is unable to predict the deformation behavior of grains, the boundary slip transmission accurately predicts the grain deformation behavior.

Correlation between pre- and post-treatments of additively manufactured 316L parts and the resulting low cycle fatigue behavior - Garthe, Kai-Uwe; Hoyer, Kay-Peter; Hagen, Leif; Tillmann, Wolfgang; Schaper, Mirko (Rapid Prototyping Journal)
Purpose The currently existing restrictions regarding the deployment of additively manufactured components because of poor surface roughness, porosity and residual stresses as well as their influence on the low-cycle fatigue (LCF) strength are addressed in this paper. Design/methodology/approach This study aims to evaluating the effect of different pre- and post-treatments on the LCF strength of additively manufactured 316L parts. Therefore, 316L specimens manufactured by laser powder bed fusion were examined in their as-built state as well as after grinding, or coating with regard to the surface roughness, residual stresses and LCF strength. To differentiate between topographical effects and residual stress-related phenomena, stress-relieved 316L specimens served as a reference throughout the investigations. To enable an alumina coating of the 316L components, atmospheric plasma spraying was used, and the near-surface residual stresses and the surface roughness are measured and investigated. Findings The results have shown that the applied pre- and post-treatments such as stress-relief heat treatment, grinding and alumina coating have each led to an increase in LCF strength of the 316L specimens. In contrast, the non-heat-treated specimens predominantly exhibited coating delamination. Originality/value To the best of the authors’ knowledge, this is the first study of the correlation between the LCF behavior of additively manufactured uncoated 316L specimens in comparison with additively manufactured 316L specimens with an alumina coating.

Novel AgCa and AgCaLa alloys for Fe-based bioresorbable implants with adapted degradation - Krüger, Jan Tobias; Hoyer, Kay-Peter; Filor, Viviane; Pramanik, Sudipta; Kietzmann, Manfred; Meißner, Jessica; Schaper, Mirko (Journal of Alloys and Compounds)
Resorbable implants are highly beneficial to reduce patient burden since they need not be removed after a defined period. Currently, magnesium (Mg) and polymers are being applied as bioresorbable materials. However, for some applications the insufficient mechanical properties and high degradation rate of Mg cause the need for new materials. Iron (Fe)-based alloys are promising due to their biocompatibility and good mechanical properties, but their degradation rate is too low and needs to be adapted eg. via alloying with manganese (Mn). Besides, phases with high electrochemical potential lead to increased degradation of residual material with lower potential based on the galvanic coupling. Here, silver (Ag) is promising for the formation of such phases due to its high electrochemical potential (+0.8 V vs. SHE), immiscibility with Fe, biocompatibility, and anti-bacterial properties. Since remaining silver particles can lead to adverse consequences as thrombosis, these particles need to dissolve after the matrix material. Thus a silver alloy with high electrochemical potential, biocompatibility, and adjusted degradation behavior is required as an additive for iron-based bioresorbable materials. Several silver alloying systems are possible, but regarding the electrochemical potential and degradation behavior of binary alloys, calcium (Ca) and lanthanum (La) are best-suited considering their biocompatibility. Accordingly, this research addresses AgCa and AgCaLa alloys as additives for iron-based degradable materials with adapted degradation behavior.

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Time efficient laser modification of steel surfaces for advanced bonding in hybrid materials - Voswinkel, Dietrich; Kloidt, D.; Grydin, Olexandr; Schaper, Mirko (Production Engineering)
Abstract Laser surface treatment of metals is one option to improve their properties for adhesive bonding. In this paper, a pulsed YVO4 Laser source with a wavelength of 1064 nm and a maximum power of 25 W was utilized to increase the surface area of the steel HCT490X in order to improve its bonding properties with a carbon fibre reinforced polymer (CFRP). Investigated was the influence of the scanning speed of the laser source on the bonding properties. For this purpose, the steel surfaces were ablated at a scanning speed between 1500 and 4500 mm/s. Afterwards the components were bonded with the adhesive HexBond™ 677. After lap shear tests were carried out on the specimen, the surfaces were inspected using scanning electron microscopy (SEM). The experiments revealed that the bonding quality can be improved with a high scanning speed, even when the surface is not completely ablated.

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang (ChemElectroChem)

Laser beam melting of functionally graded materials with application-adapted tailoring of magnetic and mechanical performance - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materials Science and Engineering: A)

Quasi in-situ analysis of fracture path during cyclic loading of double-edged U notched additively manufactured FeCo alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Schaper, Mirko (International Journal of Fatigue)

Investigating the microstructure of an additively manufactured FeCo alloy: an electron microscopy study - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Additive Manufacturing)

Characterization of phase transformations during graded thermo- mechanical treatment of steel 22MnB5 by means of optical methods - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Materials Data for Smart Forming Technologies)

Plattdeutsch im Kreis Höxter. "Der Dialektatlas Mittleres Westdeutschland (DMW)" und die Frage "Wie klingt Plattdeutsch im Kreis Höxter?" - Wallmeier, Nadine (Kreis Höxter Jahrbuch)

Das paderbörnische Platt. Niederdeutsch im Gebiet der Kreise Paderborn und Höxter - Tophinke, Doris; Wallmeier, Nadine; Merten, Marie-Luis

Theoriekonformität von Unterrichtsplanungen im Fach Physik vor und nach dem Praxissemester - Mutschler, Tanja; Buschhüter, David; Schröder, Jan; Riese, Josef; Borowski, Andreas (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020)

Erwerb physikdidaktischen Wissens zum Einsatz digitaler Medien im Physikunterricht - Große-Heilmann, Rike Isabel; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020. Essen: Universität Duisburg-Essen)

Längsschnitt Physikdidaktischen Wissens: Ursachen für Veränderungen - Joswig-Käfer, Ann-Kathrin; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020. Essen: Universität Duisburg-Essen)